Determinants of smallholder farmers' participation and level of participation in small-scale irrigation practice in Gemechis district, West Hararghe Zone, Ethiopia. Issue 1 (1st January 2021) - Geddafa, Tale; Abera, Emebet; Gedefa, Fikire
Abstract: The study was conducted to assess factors that determine a household's participation and intensity of use in the Gemechis district. A multi-stage sampling technique was employed and 167 sample households were selected by using the Cochran formula. Both quantitative and qualitative data types from primary and secondary sources were collected. Cross-sectional data were gathered through a semi-structured questionnaire survey. For both dummy and continuous variables, chi-square (χ2) and independent t-test statistics were used, respectively, to test the significance of the mean value of the two groups of participants and non-participants. The double hurdle model was used to analyze determinants of farmers' decision to participate and intensity of use of small-scale irrigation practice. Results of the first part of the double hurdle (probit) model revealed that the sex of household heads, household size, the annual income of the household, farm distance from the water source, access to extensions, and credit services were found to significantly determine the participation decisions of farmers in the small-scale irrigated agriculture, at different significance levels. In the second part of the double hurdle (truncated) model indicates household size, access to own oxen, farming experience, and access to credit services were found to significantly determine the intensity of participation in small-scale irrigated farming, at different significance levels. Results further showed that farm distance from irrigation water was found to be a barrier for participation in irrigation with significant effect. Therefore, groundwater development and rainwater harvesting ponds should be practiced close to the irrigation land.